Training on Submitting in Accredited National Journals Publication for Biology Education Students at FKIP Untan - Eko Sri Wahyuni, et. al. (JPKM (Jurnal Pengabdian Kepada Masyarakat) UNTAN, 2021)
The Circular of the Director-General of Higher Education No. 152/E/T/2012 contains the mandatory scientific publications for undergraduate/S2/S3 students as one of the graduation requirements. This circular is effective starting after graduation after August 2012. Since the regulation on scientific publications for these students was enacted, the biology education study program of FKIP Untan also enforced rules for publishing student research results in scientific journals. Based on the obstacles faced by students, this PKM is focused on providing training to students, how to submit articles to accredited national journals, and providing tips and tricks so that articles made by students can be accepted and published in accredited national Scopus indexed international journals. This program aims to help and train teacher candidates to publish articles made in accredited national journals and international journals. The stages in this activity are planning, implementation, observation, and reflection. The implementation stage has been carried out through the "Workshop Submit and Publication of Accredited National Journals for Biology Education Students" held on June 12, 2021, attended by 200 students of all generations. This activity is expected to help students in choosing journals. Submitting and publishing scientific articles on the results of research that has been carried out.